2016
DOI: 10.3791/53695
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mouse Hippocampal Astrocytes after <em>In-Vitro</em> Ischemia

Abstract: Astrogliosis following hypoxia/ischemia (HI)-related brain injury plays a role in increased morbidity and mortality in neonates. Recent clinical studies indicate that the severity of brain injury appear to be sex dependent, and that the male neonates are more susceptible to the effects of HI-related brain injury, resulting in more severe neurological outcomes as compared to females with comparable brain injuries. The development of reliable methods to isolate and maintain highly enriched populations of sexed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Taken together, our findings indicate that microglial depletion aggravates neuronal death due to a lack of anti-inflammatory cytokines. However, other sex-related mechanisms may inhibit neuronal damage in females, including the mitochondrial respiratory capacity of astrocytes, as well as the different contribution of TGF-β by resident microglia [55,65,66]. Consistent with our findings, Jin reported that microglial depletion increased ischemia-induced astrocytic inflammatory response and neural injury [26].…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, our findings indicate that microglial depletion aggravates neuronal death due to a lack of anti-inflammatory cytokines. However, other sex-related mechanisms may inhibit neuronal damage in females, including the mitochondrial respiratory capacity of astrocytes, as well as the different contribution of TGF-β by resident microglia [55,65,66]. Consistent with our findings, Jin reported that microglial depletion increased ischemia-induced astrocytic inflammatory response and neural injury [26].…”
Section: Discussionsupporting
confidence: 89%
“…Notwithstanding, the absence of pericellular O 2 measurements makes it virtually impossible to ascertain whether there is a higher concentration of oxygen in the control group and by what margin. This makes any interpretation of the results complicated, especially because the cell cultures used in these studies for their sensitivity to ischemic hypoxic injury, such as cardiomyocytes (132), neurons (137), kidney (138), and endothelial cells (139), tend to have relatively high oxygen consumption rates (85). Moreover, these studies generally do not include information about the height of the medium overlay above the adherent cell culture, which introduces yet another unknown variable that possibly affects the results and reproducibility (17,18).…”
Section: Downsides Of Conventional Systemsmentioning
confidence: 99%